Sosialisasi Serbuk Penjernih Air Gambut di Kelurahan Industri Tenayan Kecamatan Tenayan Raya Kota Pekanbaru - Budijono Budijono; Isma Mulyani; Yuliati Yuliati; Eko Purwanto; Andri Hendrizal; Yudho Harjoyudanto; Rina D'rita Sibagariang (PELANTAR PRESS, 2024)
Riau is known for its peaty waters, which often pose a challenge in providing clean water to the community. This activity aims to introduce a simple yet effective technology in purifying peat water using specially formulated magic powder. The methods used in this activity include counseling, demonstration of the use of peat water purification magic powder, and interactive discussions with participants. The participants of this activity were the local community who were very enthusiastic about participating in the whole series of events. The results of this activity showed an increase in community knowledge and understanding of the importance of clean water quality and an easy way to purify peat water using magic powder. Evaluation of the participants' understanding was conducted through questionnaires before and after the activity. The evaluation results showed that most participants were able to understand and apply the peat water purification method correctly. This activity is expected to be sustainable and have a positive impact on the health and quality of life of the community in Tenayan Industrial Village.